Application of bio-resorbable membranes in preventing complications of lower jaw surgery - Tušek Ivan; Pohodenko-Chudakova Irina; Tserakhava Nikolaevna; Maksimovich Ekaterina; Karsyuk Yuri; Savich Alexander; Mladenović Raša (Balkan Stomatological Society, 2022)
Background/Aim: Prevention of inflammation and alveolar bone atrophy is very important in oral surgery. The aim of this study was to compare the use of two osteoplastic bio-resorbable membranes in order to prevent inflammatory complications and atrophy of the alveolar part of the mandible after surgical interventions. Material and Methods: We examined 86 patients 45-70 years old who were classified into four groups. In group 1, there were 21 patients who had a "bio-resorbable membrane type 1 implanted. The group 2 consisted of 23 persons treated with bio-resorbable membrane type 2. Only the occurrence of inflammatory complications after the placement of these membranes was monitored. Group 3 included 20 persons treated with membrane type 1 and group 4 included 22 patients treated with membrane type 2 to prevent both inflammatory complications and atrophy of the alveolar part of the mandible. The level of atrophy of the alveolar bone after one year was determined by cone-beam computed tomography. The obtained data were statistically evaluated. Results: Six inflammatory complications ("dry socket") have been identified in operated patients treated with a membrane type 1 (the first and the third groups). Only two "dry socket" occurred in patients treated with membrane type 2 (the second and fourth groups). Group 4 had significant advantages in the alveolar crest height 14.6 (11.2-22.3) and in its width 7.7 (5.1-10.2) both in relation to the indices of group 3 (11.1 (9.7-20.4) and 6.2 (4.2-9.0). Conclusions: The bio-resorbable membrane type 2 prevented inflammatory complications in the short postoperative period after surgical interventions, as well as, the atrophy of the mandible.